Anesthetic management in a challenging case of primary pulmonary synovial sarcoma - Singh, Pooja; Verma, Ankur; Biswas, Shubhashish; Tyagi, Tarun; Dabas, Surender Kumar (International Journal of Research in Medical Sciences, 2024)
Primary pulmonary synovial sarcoma is a very rare tumor. This tumor accounts for less than 0.5% of all lung neoplasia. While synovial sarcomas are commonly reported from periarticular tissues, they are often found in lung or thorax as a metastasis from an extrapulmonary primary. However, rarely they arise primarily from lung tissue. We report a case of primary pulmonary synovial sarcoma which was indenting the right side of the heart. He was managed with neoadjuvant chemotherapy followed by surgical resection. The anesthetic management was challenging. The focus was kept on stringent invasive as well as non-invasive monitoring of cardiac and respiratory parameters. The surgery was uneventful and the patient made a successful recovery.